THE ANALYSIS OF FIRE ENGINEERING AND ADMINISTRATIVE CONTROL AT BUILDING X UNIVERSITY Y YEAR 2018 - Fandita Tonyka Maharani; Azizah Musliha Fitri; Arga Buntara (The Indonesian Journal of Occupational Safety and Health, 2019)
Jakarta Provincial Fire and Rescue Agency mentioned that the capital approximately has 900 high building, however only 20 % of them possessed adequate safety precaution. Data from the Jakarta Provincial Fire and Rescue Agency show that in 2018, 1,106 fire cases caused economic loss worth around Rp 151,498,186,111. Building X University Y is used every day with more than 500 occupants for education purpose. The aim of this study was to analyze fire engineering and administrative controls in the building according to the standards (National Fire Protection Association standards and the Regulation of Minister of Public Works No. 26/PRT/M/2008). This study used analytical descriptive design with direct observation as study method. The study was conducted in July 2018. The study found that the building has not met the adequate standards yet, such as active and passive protection systems, and the means of the evacuation system. There were no active protection systems. The only implemented passive protection system was a compartmentation system which divided the building into cells designed to resist the fire spread when it happens. There were no other passive protection systems found in the structure. All doors and windows were made of woods and glasses. There were no means of evacuation in the building. There were no administrative controls in the building. Appropriate controls are required in the building, involving fire engineering and administrative controls because the building lack of fire protective and precaution systems.Keywords: evacuation system, fire control, protection system